Pengaruh Kepercayaan Konsumen dan Komitmen Konsumen Terhadap Niat Beli Produk Elektronik di Bandung, Jawa Barat - Anora, Ayu; Setiadi, Sandi; Maulana, Rizky; Ginanjar, Noornissa Sarah (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
This research aims to investigate the impact of customer trust and commitment on the purchase intentions of consumers regarding electronic products in Bandung, West Java. The respondents for this study consisted of 100 consumers of electronic products in the city of Bandung, West Java, selected through convenience sampling. The analytical model employed in this research is multiple linear regression. The findings of the regression analysis reveal a positive influence of both trust and commitment on the purchase intentions of consumers of electronic products in the city of Bandung, West Java. Moreover, it is observed that both trust and commitment significantly contribute to purchase intentions individually, with a significance level of α= 0.05.